The impact of altered haemodynamics on the development of the epicardium - Perdios, Chrysostomos (2019)
During embryo development the heart is the first functioning organ. Although quiescent in the adult heart, the epicardium is essential during development to form a normal functioning heart. Epicardial derived cells contribute to the heart as it develops, including fibroblasts and vascular smooth muscle cells. Previous studies have shown that a heartbeat is required for epicardium formation. Further, preliminary studies from our laboratory have shown that the development of the epicardium is aberrant when the haemodynamics are altered.